2013
DOI: 10.3109/10428194.2013.780655
|View full text |Cite
|
Sign up to set email alerts
|

Single-center analysis of biopsy-confirmed posttransplant lymphoproliferative disorder: incidence, clinicopathological characteristics and prognostic factors

Abstract: Hematopoietic stem cell and solid organ transplant recipients diagnosed with biopsy-confirmed posttransplant lymphoproliferative disorder (PTLD) at our institution from 1989 to 2010 were identified. Patient-, transplant- and disease-related characteristics, prognostic factors and outcome were collected and analyzed. One hundred and forty biopsy-proven cases of PTLD were included. Overall incidence in the transplant population was 2.12%, with heart transplant recipients carrying the highest risk. Most PTLDs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
104
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 30 publications
8
104
1
1
Order By: Relevance
“…The time from transplant to diagnosis of PTLD typically was < 1 year in early reports and longer in more recent studies. 11 In the present study, most patients were diagnosed with PTLD > 1 year after transplant.…”
Section: Discussionmentioning
confidence: 79%
“…The time from transplant to diagnosis of PTLD typically was < 1 year in early reports and longer in more recent studies. 11 In the present study, most patients were diagnosed with PTLD > 1 year after transplant.…”
Section: Discussionmentioning
confidence: 79%
“…The risk factors for developing PTLD include EBV serostatus (higher risk of developing PTLD when an EBV seronegative organ recipient receives an organ from a seropositive donor), type of organ transplant, intensity of immunosuppression and age: There is a higher incidence of PTLD among extrarenal transplant recipients (5-7); the incidence of PTLD is highest with haploidentical hematopoietic stem cell transplant (HSCT), heart/lung and multivisceral transplants (≤20%), followed by liver (4.5%), combination heart-lung (2.5%), pancreas (2%), kidney (1-1.5%) and matched related and unrelated HSCT (0.5-1%) (7,8); in addition, pediatric patients are at greater risk compared with adults (5).…”
Section: Discussionmentioning
confidence: 99%
“…3 In our series, most malignancies were categorized as PTLD, which typically occurs with advanced disease and frequent extranodal involvement. 4 Our previous study showed that 33% patients were diagnosed with nodal PTLD. 5 The risk of Kaposi sarcoma in transplant recipients parallels Human herpesvirus 8 (HHV-8) seroprevalence in different countries and regions.…”
Section: Discussionmentioning
confidence: 99%